A Bacterial Expression Vector Archive (BEVA) for Flexible Modular Assembly of Golden Gate-Compatible Vectors - Geddes, Barney A.; Mendoza-Suárez, Marcela A.; Poole, Philip S. (Frontiers in Microbiology, 2019)
We present a Bacterial Expression Vector Archive (BEVA) for the modular assembly of bacterial vectors compatible with both traditional and Golden Gate cloning, utilising the Type IIS restriction enzyme Esp3I and have demonstrated its use for Golden Gate cloning in Escherichia coli. Ideal for synthetic biology and other applications, this modular system allows a rapid, low-cost assembly of new vectors tailored to specific tasks. Using the principles outlined here, new modules for specific applications, e.g. origin of replication for plasmids in other bacteria, can easily be designed. It is hoped that this vector construction system will be expanded by the scientific community over time by creation of novel modules through an open source approach. To demonstrate the potential of the system three example vectors were constructed and tested. Golden Gate level 1 vectors; pOGG024, with a broad-host range and high copy number was used for gene expression in laboratory-cultured Rhizobium leguminosarum, and pOGG026, with a broad-host range a lower copy number and excellent stability, even in the absence of antibiotic selection. The application of pOGG026 is demonstrated in environmental samples by bacterial gene expression in nitrogen-fixing nodules on pea plants roots formed by R. leguminosarum. Finally, the level 2 cloning vector pOGG216 is a broad-host range, medium copy number, for which we demonstrate an application by constructing a dual reporter plasmid expressing green and red fluorescent proteins.